A Biomechanical Comparison of Screw and Plate Fixations for Scaphoid Fractures - Goodwin, Jill; Castañeda, Paulo; Drace, Patricia; Edwards, Scott (Journal of Wrist Surgery, 2018)
Background Headless screw fixation is the current gold standard of surgical repair for scaphoid fractures. However, maintaining reduction of certain types of scaphoid fractures is challenging with a compression screw. Plate fixation may offer superior fixation in some scaphoid fractures, particularly those with comminution, nonunion, segmental bony defects, and osteopenic or osteoporotic bone.Purpose This study questions whether method of fixation is a determinant in load to failure in segmental scaphoid fractures, and whether any fixation provides a greater mechanical advantage in simulated normal versus osteoporotic bone.Materials and Methods Polyurethane models were fashioned to simulate scaphoids with 3-mm segmental defects. Defects were bridged by one of three constructs: a locking plate, a nonlocking plate, or a headless compression screw. Three models for each fixation construct were tested for both simulated normal and osteoporotic bone density. Load to failure was recorded as the load at which the 3-mm segmental defect was closed.Results Gap closure occurred in all trials. In simulated normal bone, there were no statistically significant differences in load to failure between fixation methods. In simulated osteoporotic bone, the locking plate had a 28% greater load to failure as compared with screw fixation.Conclusion While biomechanical testing shows that plate and screw fixations are equivalent in normal density bone for fixation of a segmental scaphoid defect, locking plates are superior to screw fixation in simulated osteoporotic bone models.Clinical Relevance Plate fixation may provide superior fixation for complex scaphoid fractures, particularly in osteopenic bone.
Keywords: scaphoid; nonunion; biomechanical; plate